Tense, aspect, and indexicality - Higginbotham, James (Oxford : Oxford University Press, 2010)
James Higginbotham's work on tense, aspect, and indexicality explore the principles governing demonstrative, temporal, and indexical expressions in natural language and present new ideas in the semantics of sentence structure.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Grammar, Comparative and general -- Aspect; Indexicals (Semantics); Grammar, Comparative and general -- Tense; Semantics (Philosophy); Language and languages -- Philosophy